DIASPORIC CULTURE AND INTERNATIONAL RELATIONS-A HISTORICAL STUDY - Manzoor Bhat, Rashid; Rajeshwari, Dr. R. (Universitas Efarina, 2022)
Ethnic or national groups that have dispersed to other nations are called diasporas. Since ancient times, they have influenced world politics, and they still do so today. Diasporas are non-state actors that engage in interactions with states, particularly their host state—the nation they currently call home—and their homeland. They play a special role in international relations because they live between two countries, share two cultures, care deeply about two countries, and uphold social ties between two societies. Diasporas can influence both domestic and global politics as organised groups with a strong sense of identity. Regarding domestic politics, they have the ability to have an impact on both the politics of their home countries and the politics of the countries they are visiting. They have the power to affect both international organisation and national foreign policy decisions in the area of international relations.